2024
DOI: 10.1007/s13668-024-00517-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed Food and Obesity: What Is the Evidence?

Samuel J. Dicken,
Rachel L. Batterham

Abstract: Purpose of Review Obesity is a growing global healthcare concern. A proposed driver is the recent increase in ultra-processed food (UPF) intake. However, disagreement surrounds the concept of UPF, the strength of evidence, and suggested mechanisms. Therefore, this review aimed to critically appraise the evidence on UPF and obesity. Recent Findings Observational studies demonstrate positive associations between UPF intake, weight gain, and overweight/obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 121 publications
0
16
0
Order By: Relevance
“…In fact, according to the study by Hall (28), the weekly cost to prepare a diet of 2000 Kcal/day consisting of ultraprocessed foods was US$ 106, compared to US$ 151 for an unprocessed diet. Therefore, it has been suggested that policies to reduce UPF intake take into account the most vulnerable groups to avoid deepening economic, health, and social inequalities (33). Strategies have been proposed, such as including these groups in food assistance programs to improve access to natural and minimally processed foods (2), as well as reformulating UPFs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, according to the study by Hall (28), the weekly cost to prepare a diet of 2000 Kcal/day consisting of ultraprocessed foods was US$ 106, compared to US$ 151 for an unprocessed diet. Therefore, it has been suggested that policies to reduce UPF intake take into account the most vulnerable groups to avoid deepening economic, health, and social inequalities (33). Strategies have been proposed, such as including these groups in food assistance programs to improve access to natural and minimally processed foods (2), as well as reformulating UPFs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the extrusion and retrogradation of starch affect the availability of carbohydrates, while particle size and viscosity influence glycemic response, whose postprandial level can impact appetite and fat storage in the liver and skeletal muscle, which is associated with the development of insulin resistance (47,57). Furthermore, ultra-processing modifies the texture of foods, making them softer and easier to consume, promoting continuous and unconscious eating behaviors (46), and a faster energy intake that affects satiety, transit time, digestibility, and nutrient bioavailability (2,33). These relationships could be due to inadequate signaling of satiety sensations to the brain, the release of hormones that regulate hunger and satiety, and a shorter gastric emptying time that increases the speed at which nutrients are released and absorbed in the body (58,59).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations